Pathogenicity of Colletotrichum truncatum and its influence on soybean seed quality - M. M., Begum; Meon , Sariah; Puteh, Adam; Mior Ahmad, Zainal Abidin (2008)
Pathogenicity of Colletotrichum truncatum and its influence on soybean seed quality were evaluated by artificial inoculation. C. truncatum enabled to establish as latent infection without showing any visible symptom in all seed components with maximum frequency values of 100% for seed coat, 43.0% for cotyledon and 30.0% for embryonic axes after 4 days of incubation period. The infection level remained the same in all seed components until the end of the incubation period. Fungal infection reduced seed germination by 29.2% and viability by 26.9% than un-inoculated seeds in vitro. Moreover, infection increased the electrolyte leakages compared with control. Under glasshouse conditions, pathogenicity of C. truncatum on seeds and seedlings was more virulent than that of controlled conditions. In the glass house, C. truncatum reduced seed germination and seedling survival by 46.4% and 75.8%, respectively and caused pre- and post-emergence damping-off of seedlings. However, fungal infection by C. truncatum increased protein and oleic acid content and reduced linoleic acid content, but did not change in extracted oil and other fatty acids when compared with un-inoculated seeds after 4 days of incubation.